'When we sat together, it just worked': Supporting individual and collaborative reflective practice in a team of early childhood educators. Issue 1 (March 2022) - Ruming, Naomi; McFarland, Laura
Educator reflective practice is fundamental to quality early childhood education with robust practice benefitting pedagogy and improving outcomes for children. Yet, examination of individual and collaborative reflective practice in experienced professional early childhood teams is scarce. This qualitative case study used an action research design to examine this gap in the literature. Previous research informed the implementation of a Model of Reflective Practice Framework as an intervention incorporating a professional development session and ongoing written support of individual and team educator reflection. An established team of six educators in a regional Australian preschool setting provided data through pre- and post-intervention surveys, individual journal entries, and online collaborations. Manual and computer-assisted thematic analysis was enhanced with evaluation using a continuum of reflection and by examining reflection outcomes. Results indicate improvement in individual and team reflective practice, with additional professional and personal benefits.